A colorimetric and fluorescent chemosensor for detection of Hg2+ using counterion exchange of cationic polydiacetylene. Issue 46 (15th November 2017) - Lee, Cheol Gyu; Kang, Seungyoon; Oh, Jinyoung; Eom, Min Sik; Oh, Jusung; Kim, Min-Gon; Lee, Woon Seob; Hong, Sukwon; Han, Min Su
Graphical abstract: Highlights: A chemosensor for Hg 2+ was developed using counterion exchange of cationic PDA. It shows colorimetric and fluorescence response toward Hg 2+ and allows naked-eye detection. It is applied to determine Hg 2+ concentrations in tap water samples. Abstract: In this study, a colorimetric and fluorescent chemosensor for mercury ions (Hg 2+ ) was developed. Cationic polydiacetylene (PDA) vesicles with a quaternary ammonium cation and iodide as a counterion show a blue-to-red color transition; the color change is accompanied by a fluorescence enhancement in selective response to Hg 2+ ions because of a perturbation of the ene–yne conjugated backbone induced by counterion exchange. It allows for selective detection of Hg 2+ with the naked eye and the sensor is used to determine Hg 2+ concentrations in tap water samples.